State of industrial - Hechanova, Ma. Regina M.
This article traces the roots of IO psychology. Based on archival data, interviews and a review of literature, it presents the state of education, research and practice in IO psychology. The articles highlights the challenges that IO psychologists face and the implications for the growth of the field in the country.